2021
DOI: 10.1111/1467-8551.12536
|View full text |Cite
|
Sign up to set email alerts
|

Managing the Crisis: How COVID‐19 Demands Interact with Agile Project Management in Predicting Employee Exhaustion

Abstract: As a global pandemic, COVID‐19 impacts work‐related processes, placing strain upon many employees in project teams. Identifying process variables and potential organizational resources can play an important role in addressing employee mental health, both for the current pandemic and future crises. Based on an extension of the job demands–resources model, this paper introduces COVID‐19 demands as distal job demands, examining their influence on emotional exhaustion through proximal unfinished tasks. Furthermore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
41
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(42 citation statements)
references
References 72 publications
0
41
0
1
Order By: Relevance
“…Organizations which are capable of rapidly adapting to the changes occurring in the environment by operating based on agile methodologies deal better with the current crisis than companies operating based on traditional patterns [42]. The use of agile project management methodologies also alleviates feelings of emotional exhaustion resulting from the pressure of work on project teams during the COVID-19 pandemic [43] and supports the development of Industry 4.0, and thus Healthcare 4.0 [44]. In the healthcare sector agility, plays a vital role in COVID-19 care to enhance the operational performance to meet the dynamic demand of COVID-19 hospitals [45].…”
Section: Literature Review and Research Questionsmentioning
confidence: 99%
“…Organizations which are capable of rapidly adapting to the changes occurring in the environment by operating based on agile methodologies deal better with the current crisis than companies operating based on traditional patterns [42]. The use of agile project management methodologies also alleviates feelings of emotional exhaustion resulting from the pressure of work on project teams during the COVID-19 pandemic [43] and supports the development of Industry 4.0, and thus Healthcare 4.0 [44]. In the healthcare sector agility, plays a vital role in COVID-19 care to enhance the operational performance to meet the dynamic demand of COVID-19 hospitals [45].…”
Section: Literature Review and Research Questionsmentioning
confidence: 99%
“…Scholars report psychological symptoms induced by remote working during the pandemic ranging from stress, emotional distress, emotional exhaustion, and anxiety to depression ( 4 , 32 , 34 ). Employees' mental health issues are associated with their perceptions of the pros and cons of telework.…”
Section: Resultsmentioning
confidence: 99%
“…On top of that, the strict management control and monitor ( 32 ), deteriorated work engagement ( 37 ), and excessive job demand ( 34 ) can aggravate employees' mental health psychological symptoms during remote working. Also, employees in developed countries (i.e., Italy, Finland, Germany, U.S., Canada, Norway, U.K., and Australia) report similar positive (4/11 articles) and negative (3/11 articles) psychological impacts.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…After all, 20.8% of the study participants stated that their ability to work is strongly affected and 13.8% agreed that they are worried about their job because of the Corona crisis. However, research has shown that agile project management acted as a buffering job resource in the relationship between COVID-19 demands and emotional exhaustion [95]. From this, it can be assumed that the pandemic situation has strengthened the effects rather than weakened them.…”
Section: Limitations and Future Researchmentioning
confidence: 99%